Characterization of soundscape perception of preschool children. (15th April 2022) - Ma, Hui; Su, Hua; Cui, Jiaao
Abstract: To characterize their soundscape perception, preschool children were subjected to inclusive soundscape exposure conditions (both indoor and outdoor) and were asked to evaluate the soundscape in this study comprising two experiments. In Experiment 1, reliable soundscape perception dimensions for preschool children were formulated using semantic differential analysis. In Experiment 2, the relationship between the dimensions and the overall soundscape evaluation and acoustic characteristics was investigated. The principal component analysis resulted in three factors (eigenvalue> 1), namely pleasantness, peacefulness, and regularity, explaining 69.96% of the variance (48.70%, 13.13%, and 8.13%, respectively). Among them, pleasantness and peacefulness significantly contributed to the overall soundscape evaluation (preference), as the improvement attitude of these two factors led to a higher chance of a positive attitude towards the overall soundscape preference (i.e., "like"). LA50 and LA10 contributed significantly to the regression for pleasantness and peacefulness, accounting for 41.2% and 92.6% of the prediction variance, respectively. Regularity had no significant effect on the overall soundscape evaluation. In addition, no acoustic characteristics significantly predicted this factor. The outcome showed that preschool children are capable of multi-scale evaluation of diverse soundscapes, embodying their awareness of both the quality and influence of the acoustic environment. Their soundscape perception dimensions pertain to the features of the preschool period and are thus inconsistent with previous adults' soundscape dimensions. In addition, preschool children seem to desire mild and peaceful soundscapes under control. Highlights: Preschool children reported their perception of both indoor and outdoor soundscapes. Preschoolers' soundscape perception dimensions: Pleasantness, Peacefulness, and Regularity. Pleasantness and Peacefulness influenced the overall soundscape evaluation. LA50 significantly contributed to the regression for Pleasantness. LA10 significantly contributed to the regression for Peacefulness.